Possibilities and challenges in developing and implementing an empowerment-based school-intervention in a Swedish disadvantaged community. (8th March 2019) - Jonsson, L; Fröberg, A; Korp, P; Larsson, C; Berg, C; Lindgren, E -C
Abstract: In this paper, we describe and critically reflect on the possibilities and challenges of developing and implementing an empowerment-based school intervention regarding healthy food and physical activity (PA), involving participants from a Swedish multicultural area characterized by low socioeconomic status. The 2-year intervention was continually developed and implemented, as a result of cooperation and shared decision making among researchers and the participants. All 54 participants were seventh graders, and the intervention comprised health coaching, health promotion sessions and a Facebook group. We experienced that participants valued collaborating with peers, and that they took responsibility in codeveloping and implementing the intervention. Participants expressed feeling listened to, being treated with respect and taken seriously. However, we also experienced a number of barriers that challenged our initial intentions of aiding participation and ambition to support empowerment. Moreover, it was challenging to use structured group health coaching and to work with goal-setting in groups of participants with shared, and sometimes competing, goals, wishes and needs related to food and PA. Successful experiences from this intervention was the importance of acquiring a broad and deep understanding of the context and participants, being open to negotiating, as well as adjusting the intervention.